2017
DOI: 10.1007/s11010-017-3078-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of damage-associated molecular patterns (DAMPs) in osteoarthritis of human knee joint compared to hip joint

Abstract: Osteoarthritis (OA) is a degenerative disease characterized by the destruction of cartilage. The greatest risk factors for the development of OA include age and obesity. Recent studies suggest the role of inflammation in the pathogenesis of OA. The two most common locations for OA to occur are in the knee and hip joints. The knee joint experiences more mechanical stress, cartilage degeneration, and inflammation than the hip joint. This could contribute to the increased incidence of OA in the knee joint. Damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 52 publications
2
45
0
2
Order By: Relevance
“…inherent to the pathology underlying the need for surgery (18) and in line with the increased MMP-9 and increased TIMP-1 observed in the preoperative patient samples compared with the healthy controls ( Supplementary Fig. S3).…”
Section: Discussionsupporting
confidence: 55%
“…inherent to the pathology underlying the need for surgery (18) and in line with the increased MMP-9 and increased TIMP-1 observed in the preoperative patient samples compared with the healthy controls ( Supplementary Fig. S3).…”
Section: Discussionsupporting
confidence: 55%
“…A total of 4376 abstracts were screened, and 168 articles were selected for full‐text article screening (Figure 1). After full‐text article screening, 66 articles were included in the systematic review as they fulfilled all selection criteria 13,15,23‐27,32‐91 . Although most studies focused on either human musculoskeletal disease (n = 31) or animal models of musculoskeletal disease (n = 31), four studies investigated HMGB1 in both human and animal models of musculoskeletal disease (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…There were 35 studies that investigated HMGB1 in human musculoskeletal diseased tissue, including arthritis (27), fractures (1), IVD degeneration (4), tendinopathy (2), and frozen shoulder (1) (Table 1). 23‐26,32,33,36,38,39,41‐43,45,46,56‐58,60,62,64,66,68,69,71,75‐77,80‐82,85,88‐91 Most studies that investigated HMGB1 expression (26/28) showed that HMGB1 expression is increased in human musculoskeletal diseased tissues compared to control tissues (Table 3). 24‐26,32,33,36,38,39,41‐43,45,46,56‐58,60,62,64,66,68,69,71,75‐77,80‐82,85,88,89,91 The redox status of HMGB1 was not investigated in these studies of human musculoskeletal disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes mellitus is known to cause crosslinking of collagen due to the formation of AGEs [24]. A recent study has shown increased expression of damage-associated molecular patterns (DAMPs), including high-mobility group box-1, the receptor for advanced glycation end products, and alarmins (S100A8 and S100A9) in the knee compared to the hip joint [30]. This is thought to facilitate increased cartilage degradation and inflammation.…”
Section: Discussionmentioning
confidence: 99%